Development and Functional Characterization of Monoclonal Antibodies for Botulinum Neurotoxin Serotype A - Jingmei Kang; Qingyu Lv; Wenhua Huang; Hua Jiang; Shan Gao; Qian Li; Decong Kong; Guofen Zhao; Peng Liu; Yongqiang Jiang (Foods)
Botulinum neurotoxin serotype A (BoNT/A), the most toxic of the seven serotypes produced by Clostridium botulinum, poses significant public health risks because of its involvement in foodborne outbreaks and potential use in bioterrorism. In this study, we developed high-affinity monoclonal antibodies for BoNT/A detection using single-cell fluorescence-activated cell sorting and nested PCR. The optimized antibody pair demonstrated exceptional sensitivity, detecting recombinant BoNT/A at concentrations as low as 0.02 ng/mL with a linear range of 0.02–10 ng/mL, while maintaining high specificity against BoNT/B, E, and F. Biolayer interferometry confirmed superior binding kinetics, and a time-resolved fluoroimmunoassay (TRFIA) demonstrated consistent performance in complex food matrices, including ham sausage and soybean paste. These rabbit-derived monoclonal antibodies enable ultrasensitive detection of BoNT/A across diverse food matrices, offering a powerful tool for food safety monitoring and biosecurity.